SOSIALISASI PENGENALAN HEWAN PENYU LAUT MELALUI PERMAINAN MENARIK BAGI ANAK SEKOLAH DASAR SDN ALUE PIET GAMPONG ALUE PIET - Mohamad Gazali (Universitas Teuku Umar, 2018)
Conservation is one of the activity that hope to prevent the sea turtle are scarce, to prevent sea turtle utilization for commercial interest such as sold the eggs, flesh, as well as carapaces and become sharing knowledge facility or education for community widely regarding the importance of sea turtle conservation for keeping sea turtle habitat in Indonesia in order it is not scarce. The target of communities are elementary school student SDN Alue Piet. According to the interview that many student that inhabited in Panga Pasie Coastal area still feel strange with sea turtle. Among of them ever found it in the coastal area on the morning to feel fearness with this creature that appeared strange. Therefore, we conduct the community serving through the socialization of sea turtle introduction with interesting of media game. The community serving including surveying of elementary school that approach with nesting site, socialization of sea turtle introduction through video sea turtle animation, doing of Quiz, and undertaken arrangement of sea turtle puzzle picture. Overall activities of community serving undergone on time and obtained supporting from SDN Alue Piet organizer.